ENVIRONMENTAL MANAGEMENT IN THE HINTERLANDS OF NORTHERN SAMAR - Sanico, Felisa L. (International Journal of Research -GRANTHAALAYAH, 2019)
This study investigated the perceptions of the faculty of members, school official and students in terms of environmental protection and management. It employed random sampling using survey questionnaires to gather data from the respondents. Frequency counts and percentage were used to process the data. Most of the respondents had positive responses on waste reduction and management, as the commonly used environmental protection strategy in the school. A majority of them rejected plastics and agreed that these are harmful to the environment friendly products, are materials that can be recycled, and less favored materials are the non-toxic products, and a majority of the respondents favored that individual bulk packaging is preferred than bulk packaging of products from suppliers. High percentage favored that the classrooms are designed to make use of natural ventilation and natural lighting. Most of the respondents had negative responses on the issue of planning the campus in such a way as to reduce the use of motor vehicle in terms of motor boat as mode of transportation. There was a high percentage of positive response regarding the physical greening of the school, as observed in the entire campus. A majority of the respondents had positive responses on fluorescent lamps as the commonly used source of light, than of the use of incandescent. Most of the respondents had negative response on artesian well as the source of water, and a high positive response was observed regarding local water works as the source of water for everyday use. Majority of the respondents agreed that office machines are turned off when not in use, and using the fans whenever possible also had a high positive response; only fewer respondents agreed on the usage of air conditioner. A majority of the respondents agreed that white paper is the most preferred kind of paper in the school. A majority of the respondents had positive response in using the used paper in photocopying articles as commonly used paper recycling or use of reduction program. A majority of the respondents agreed that composting biodegradable was right in the campus and wet waste sent to recyclers had a low positive response. There was a high percentage of positive response on disposable plastic utensils as the most discouraged material in the canteen. Disposable cups, disposable plates, paper napkins and plastic wrappers had also high percentage as materials discouraged in the canteen. A majority of the respondents agreed that waste segregation in the school is practiced. Most of the respondents agreed that containers for biodegradable and non-biodegradable are provided in the entire campus. A majority of the respondents favored that biodegradable materials are made to compose. Respondents favored that sealing properly before disposal of hazardous/chemicals water is done inside the campus. All the eight (8) environment concerns/themes are integrated in the curriculum. A majority of the respondents indicated that environment concerns/themes are incorporated in Music, Health and Physical Education. They are also integrated in English, Social Studies, Pilipino, and Mathematics.